2018
DOI: 10.1097/md.0000000000009968
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, open label, controlled study investigating the efficiency and safety of 3 different methods of rectus sheath block analgesia following midline laparotomy

Abstract: Background:There is a controversy regarding the efficacy of rectus sheath block (RSB). The aim of the present study was to evaluate analgesic efficacy and safety of three different methods of RSB in postoperative pain management after midline laparotomy.Methods:A prospective, randomized, controlled, open-label clinical trial with 4 parallel groups was conducted in a tertiary care hospital in Finland. A total of 57 patients undergoing midline laparotomy were randomized to the control group (n = 12) or to 1 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…In line with our ndings, studies showed that BRSB is effective in reducing the severity of postoperative pain score, analgesics consumption and increases time to rst analgesic request [24][25][26][27]. While other studies failed to demonstrate BRSB effectiveness [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…In line with our ndings, studies showed that BRSB is effective in reducing the severity of postoperative pain score, analgesics consumption and increases time to rst analgesic request [24][25][26][27]. While other studies failed to demonstrate BRSB effectiveness [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…The intermittent dosing group had lower pain at rest at 12 hours; all other time points were not significantly different. [33] Similarly, Yassin 2017 found no differences in pain scores at any time point. [29] In terms of opioid consumption at 48 hours, Purdy 2018 found a reduction among both RSB groups compared to multimodal analgesia (Figure 2), whereas Yassin 2017 found opioid consumption to be significantly lower in the epidural group compared to the RSB group (Figure 3).…”
Section: Preperitoneal Cathetersmentioning
confidence: 91%
“…[26] Both Kadam et al (2013) and Wahba et al did not use opioids in their epidural solution. [36,46] Rectus Sheath Catheters Two studies involving rectus sheath block (RSB) catheters were included with one comparing to multimodal analgesia [33] and one comparing to epidural analgesia [29]. Purdy et al had three groups: RSB with intermittent dosing, RSB with continuous infusion, and control (opioid analgesia).…”
Section: Preperitoneal Cathetersmentioning
confidence: 99%
“…A catheter may be placed at the time of block performance to extend the duration of analgesia. Catheter regimens vary, but intermittent bolus seems to be more efficacious than continuous infusion [5]. For example, 10 ml of 0.2% ropivacaine in each catheter every 4 h by a programmable pump is an efficacious and safe dose in adults.…”
Section: Catheter Techniquementioning
confidence: 99%